2016
DOI: 10.1177/0049475515624031
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis: the great mimic of rheumatic diseases

Abstract: Rheumatic manifestations may be prevalent in more than 30% of patients with infective endocarditis (IE), often predating this diagnosis by several months. A case series of five patients recorded at a tertiary care Rheumatology and Clinical Immunology unit over a period of 1 year emphasises that varied presentations of endocarditis may mimic uncommon rheumatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Congestive heart failure constitutes an independent predictor of mortality (58). A few investigators have suggested that ANCA-negative status in patients with eosinophilic granulomatosis with polyangiitis is a risk factor for cardiac involvement (59). Cardiomyopathy is the most common pattern of cardiac involvement in patients with eosinophilic granulomatosis with polyangiitis and is seen in 30% of cases.…”
Section: Eosinophilic Granulomatosis With Polyangi-mentioning
confidence: 99%
See 2 more Smart Citations
“…Congestive heart failure constitutes an independent predictor of mortality (58). A few investigators have suggested that ANCA-negative status in patients with eosinophilic granulomatosis with polyangiitis is a risk factor for cardiac involvement (59). Cardiomyopathy is the most common pattern of cardiac involvement in patients with eosinophilic granulomatosis with polyangiitis and is seen in 30% of cases.…”
Section: Eosinophilic Granulomatosis With Polyangi-mentioning
confidence: 99%
“…Aortic insufficiency is the most common valvular manifestation, followed by mitral regurgitation and aortic stenosis. Endocardial masses also have been described, mimicking primary infectious endocarditis (59,64).…”
Section: Granulomatosis With Polyangiitis and Microscopicmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical manifestations suggesting an autoimmune disease can appear in 25-42% patients with infective endocarditis, and may include arthritis, muscle and joint pain, sacroiliitis, leukocytoclastic cutaneous vasculitis and glomerulonephritis. [2][3][4] In up to 60% of the cases, the presence of hypocomplementaemia, rheumatoid factor, ANA, anti-neutrophil cytoplasma antibodies or aPL antibodies has been reported. 5,6…”
Section: Letter To the Editormentioning
confidence: 99%
“…However, superantigens induced by some bacteria, such as Staphylococcus aureus , can stimulate an immune response, which could interfere with antibody production 4. Rheumatic manifestations, such as myalgia, arthralgia and arthritis are prevalent, occurring in nearly 40% of patients with IE at presentation of weeks to months before the diagnosis of IE 5. When classic IE manifestations are less evident, patients can be misdiagnosed as having a rheumatological disease, which might lead to delayed initiation of antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%